Organization of independent work of students based on distance learning and the project method (Gumilyov Journal of Pedagogy, 2026)
The education system of any country is constantly undergoing various kinds of changes, especially now. Modern trends are emerging that help organize the educational process. The main reasons for the changes are the development of scientific and technological progress, economic and political changes that are aimed at improving the educational process, and achieving high educational indicators. One of the criteria for achieving high educational indicators is the improvement of students’ independent work, carried out in a certain system, with the partner participation of the teacher in its planning and assessment of the achievement of a specific result.Improving the independent work of teachers is necessary for the development of cognitive creative activity, as well as working with a large flow of information, acquiring knowledge, and completing tasks. In this regard, it is necessary to teach teachers independent ways of acquiring knowledge, since independent work is designed to complete the tasks of all other types of educational work, because no knowledge that has not become the object of one’s own activity can be considered the true property of the individual.Thus, Zh. Asanova identifies conditions that contribute to the activation of independent work of students, and also presents its essential features, namely, the presence of a task, the absence of direct participation of the teacher in completing the task, partial participation in the organization and management of students’ cognitive activity, and the availability of sufficient time for completing the task.And only then will the independent work of teachers become a type of activity for them, and not just a developing potential in the conditions of a systematic reduction in direct contact with the teacher in completing educational tasks.Hence, we will prepare teachers who are knowledgeable, thoughtful, and able to independently obtain and apply knowledge in practice.